Numerical simulations of casing collapse: A case study in Southern Iran. - Gholami, Raoof; Rasouli, Vamegh (WITS Press, 2012)
Collapse of casings during production has been reported on many occasions in different fields. Regardless of the root for the failure of the casings, this is due to stresses applied to the casing exceeding its ultimate strength. Failure of the casing similar to any pipe could be due to compressional, tensional, and burst or collapse forces due to various loads being applied to the casing string. Although several analytical models have been developed based on elastic or plastic approaches to estimate the ultimate strength of casing, it has been shown that these methods underestimate the casing strength. Casings’ mechanical and geometrical parameters, effective in-situ stresses, temperature, formation properties and other intervening are simultaneously required for a complete design of casing. To simulate the failure of casing in the presence of various forces, numerical modeling is a robust approach that can be employed. In this study, finite element simulation was used through the use of ABAQUS software to model the failure of casings in one of the wells located in the southern part of Iran. The results revealed that increasing the diameter to thickness (D/t) ratio decreases the ultimate strength of casing, leading to unexpected failure in the wells under consideration. It was also shown that eccentricity drastically reduces the strength of casing. Since the numerical results of current study were in an acceptable agreement with experimental studies, numerical simulation method proposed here can be used to predict the casing collapse.